How Do Underwriters Value Initial Public Offerings? An Empirical Analysis of the French IPO Market* - Roosenboom, Peter (Contemporary Accounting Research, 2007)
This paper investigates how French underwriters value the stocks of companies they bring public. Underwriters often use several valuation methods to determine their fair value estimate of the initial public offering (IPO) firm's equity. We investigate five of these valuation methods: peer group multiples valuation, the dividend discount model, the discounted cash flow model, the economic value-added method, and underwriter-specific methods. We document that underwriters base their choice for a particular valuation method on firm characteristics, aggregate stock market returns, and aggregate stock market volatility in the period before the IPO. In addition, we examine how underwriters combine the value estimates of the valuation methods they use into a fair value estimate by assigning weights to these value estimates. We demonstrate that these weights also depend on firm-specific factors, aggregate stock market returns, and aggregate stock market volatility. Finally, we show that underwriters discount their fair value estimate to set the preliminary offer price of the shares. This discount is higher for IPO firms with greater valuation uncertainty and lower for companies that are brought to the market by more reputable underwriters and that are forecasted to be more profitable.